Two-dimensional echocardiography estimates of fetal ventricular mass throughout gestation. - Aye, C; Lewandowski, A; Ohuma, E; Upton, R; Packham, A; Kenworthy, Y; Roseman, F; Norris, T; Molloholli, M; Wanyonyi, S; Papageorghiou, A; Leeson, C (Karger, 2017)
Introduction Two dimensional (2D) ultrasound quality has improved in recent years. Quantification of cardiac dimensions is important to screen and monitor certain fetal conditions. We assessed feasibility and reproducibility for fetal ventricular measures using 2D echocardiography, reported normal ranges from our cohort and compared estimates to other modalities. Materials and Methods Mass and end-diastolic volumes were estimated by manual contouring in the four-chamber view using TomTec Image Arena 4.6 in end-diastole. Nomograms were created from smoothed centiles of measures, constructed using fractional polynomials after log-transformation. Results were compared to previous studies using other modalities. Results 294 scans from 146 fetuses were included from 15+0 to 41+6 weeks gestation. 7% of scans were unanalysable and intraobserver variability was good (Intraclass Correlation Coefficients for left and right ventricular mass 0.97 (0.87-0.99) and 0.99 (0.95-1.0) respectively). Mass and volume increased exponentially showing good agreement with 3D mass estimates up to 28 weeks gestation. There was good agreement with 4D volume estimates for the left ventricle. Discussion Current state-of-the-art 2D echocardiography platforms provide feasible and reproducible fetal ventricular measures across gestation which appear to be in good agreement with previously published data from other datasets using newer modalities.